Effect of Competitive Anxiety on Decision-Making in Young Volleyball Athletes - Fortes, Leonardo de Sousa (2020)
The aim of this study was to analyze the effect of competitive anxiety on decision-make of young volleyball athletes. The sample was composed of 24 volunteers. We used the Competitive State Anxiety Inventory (CSAI-2R) to evaluate the competitive anxiety. Decision-making was evaluated in real game situation, adopting the criteria of Game Performance Assessment Instrument (GPAI). Negative correlations were found between the decision-making index and both cognitive anxiety and somatic anxiety (p<0.05). In contrast, positive correlation was revealed between self-confidence and the decision-making index (p<0.05). The findings revealed the influence of cognitive anxiety, somatic anxiety and self-confidence in the decision-making index (p<0.05). It was concluded that anxiety can be considered an intervening factor in decision-making of young male volleyball players.